Local deformations of positive-definite quadratic forms - Bondarenko, V. V.; Bondarenko, V. M.; Pereguda, Yu. N. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We give a complete description of real numbers that are $P$-limit numbers for integer-valued positive-definite quadratic forms with unit coefficients of the squares. It is shown that each of these $P$-limit numbers is realized in the Tits quadratic form of a Dynkin diagram.